HUBUNGAN KONTROL DIRI DENGAN ADIKSI MEDIA SOSIAL TIKTOK PADA SISWA KELAS X SMAN 11 JAKARTA - Fadhlih, Ahdanisa; Marsinun, Rahmiwati (Jurnal Ilmiah Global Education, 2023)
This study aims to determine the relationship between self-control and addiction to the social media TikTok in class X students of SMAN 11 Jakarta in the 2022/2023 academic year. The research method used in this study is a correlational quantitative research method to be able to see the relationship between x and y variables. The population used in this study were students of class X, totaling 216 students consisting of 6 classes (classes X1, X2, X3, X4, X5, and X6). The sampling technique in this study used a simple random sampling technique. The results of the study show that the hypothesis is accepted, meaning that there is a relationship between the x variable and the y variable. It can be seen from the results of hypothesis testing using the product moment correlation, the sig value is obtained. 0.001. Decision making based on product moment correlation test criteria is if the sig. <0.05 then correlate. Based on the results of the product moment correlation test in the table above, it can be seen that the sig. 0.001 <0.05 which means that the addiction variable with self-control variables is correlated. As for the Pearson Correlation value, it was obtained at 0.658. So it can be seen that the social media addiction variable of TikTok and the self-control variable have the same strong correlation.